Discrete Boltzmann Numerical Simulation of Simplified Urban Flooding Configurations Caused by Dam Break - La Rocca, Michele; Miliani, Stefano; Prestininzi, Pietro (Frontiers in Earth Science, 2020)
The Discrete Boltzmann Equation (DBE) is a versatile simulation method, consisting of linear advection equations, which can be applied to the Shallow Water Equations (SWE).\\ The aim of this study is to assess the accuracy of the DBE to simulate dam-break of shallow water flows in presence of obstacles.\\ Dam-break flows in presence of obstacles can be regarded as simplified models for floods in urban areas.\\ In this study three cases of dam-break flows in presence of obstacles are considered: two with an isolated obstacle and the third in presence of an idealised city.\\ The comparison between DBE and benchmark results shows a fair agreement, confirming the validity of the DBE as simulation method for the SWE.